2002
DOI: 10.1159/000047771
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Characterisation of Radiation-Induced Carotid Artery Stenosis

Abstract: Background and Purpose: To study the distribution, extent and sonographic characterisation of radiation-induced carotid artery stenosis in nasopharyngeal carcinoma (NPC) patients. Methods: The distribution of plaques, the extent of stenosis, and the sonographic characterisation of the plaque at maximum stenosis were recorded in 71 NPC patients. The results were compared with the ultrasound results of a control group of 142 patients presenting with symptoms of cerebrovascular disease or carotid bruit. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 10 publications
(10 reference statements)
3
29
0
Order By: Relevance
“…[12][13][14] Moreover, a recent study revealed that RICS lesions tend to have multiple ulcers. 9 In stark contrast, Fokkema et al 11 have suggested, on the basis of histologic analysis, that RICS plaques were predominantly stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Moreover, a recent study revealed that RICS lesions tend to have multiple ulcers. 9 In stark contrast, Fokkema et al 11 have suggested, on the basis of histologic analysis, that RICS plaques were predominantly stable.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the histologic analysis of Fokkema et al revealed the tendency of RICS plaque to be stable. [11][12][13][14] This study aimed to elucidate the relationship between the characteristics of RICS and the outcomes of the carotid artery revascularization. To this end, we correlated the results of multimodality imaging before the revascularization with the histologic characteristics of CEA specimens.…”
mentioning
confidence: 99%
“…Similar findings were shown in the investigation of Lam et al [2], in which they observed that CCA or ICA were most commonly involved (55 of 71 vs. 11 of 51; p < 0.01), followed by the external carotid artery (32 of 71 vs. 1 of 51; p < 0.01) and vertebral artery (5 of 71 vs. 0; p = 0.069). However, the most common sites of traditional atherosclerotic carotid stenosis are carotid bifurcation [27] and the proximal segment of ICA. …”
Section: Characteristics Of Radiation-induced Carotid Artery Stenosismentioning
confidence: 99%
“…Concerning the sonographic features, some differences were identified [27]. Plaques exposed to radiation are more diffuse in appearance, less shadowing, and more hypoechoic.…”
Section: Characteristics Of Radiation-induced Carotid Artery Stenosismentioning
confidence: 99%
“…[2] Our data showed that the CCA lesions were more frequently affected by XRT in our patients, in accordance with other studies. [9,16] Previous studies have shown that radiation-induced carotid stenosis is more diffuse in distribution and has a different sonographic plaque characterization (less shadowing calcification but higher incidence of hypoechoic plaque) compared with carotid stenosis without radiation exposure, [16] possibly due to instability of the plaque in the XRT patients. [17,18] Radiation dose was found to have no significant influence on the progression of atherosclerosis when a total dose of more than 40 Gy or even higher than 55 Gy was used.…”
Section: Discussionmentioning
confidence: 99%